Prevalence of Toxoplasma gondii among immunocompromised patients (heamodialysis and cancer) in the province of Thi-Qar-Iraq - Kadhim Matar AL-Rekaby, Noor; A.AL-Aboody , Bassad (University of Thi-Qar Journal of Science, 2019)
The current study was conducted in Thi-Qar province to investigate of Toxoplasma gondii prevalence among renal dialysis and cancer patients by using anti-Toxoplasmosis IgG and IgM by ELISA also the study determined of some factors that may affected the prevalence of infection, such as age, sex, marital status, place of residence and a number of chemical dosing that exposed to it cancer patient or the number of times the dialysis for renal dialysis patients. The results of the current study showed that the prevalence of toxoplasmosis in Thi-Qar province in both renal dialysis and cancer patients and control group were 28% and 36% and 24% respectively. recorded results of Enzyme Linked Immunosorbent Assay ELISA test results for a positive antibody IgG in both renal dialysis and cancer patients and control group 25% , 30% , 22% respectively. As for the IgM antibody study did not record any positive result in both categories of the study (dialysis and cancer) only control group was 2%. The result of IgG & IgM together in renal dialysis and cancer and control group 3%, 6%, 0% respectively. The study found that the increase in the number of times the dialysis increased incidence of infection prevalence it was 25.53% for patients who conducted the dialysis treatment more than six times and 16.66% for patients who have less than six times.For factor chemical dosing show high infection rates in patients who have been exposed to more than one dose of a chemical 37.63% As for those who were not exposed to any chemical dose was ratios have 14.29% .